Kekurangan Manusia Dalam Pandangan Alquran - Alpi Aryf; Arrel Dwi Rizki; Muhammad Abdul Hafizh; Desi Mayang Sari; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This article was written with the aim of studying human weaknesses according to the Koran. The rules used are literary rules based on thematic interpretation (maudu'i), namely collecting verses from the Koran that talk about the same topic, then discussing them systematically. The method used in this research is a qualitative method with a library research approach. Sources of research and information in this research are the latest books, magazines and journals. The results of this research show that there is an impact of human deficiencies in the view of the Al-Qur'an which focuses on physical, intellectual, heart and lust.